Estudo da variação Metabolômica das folhas do guaraná (Paullinia Cupana) em resposta ao estresse biótico - Sousa, Joyce Ellen de Almeida (2016)
Guarana, Paullinia cupana, is a Brazilian native plant whose seeds are used to produce a wide range of food products and to be rich in caffeine is consumed mainly for its stimulating activity, which creates a great potential for the market, being produced and marketed mainly by Amazon states. Guarana metabolic profile is rich in phenolic compounds of flavonoid class which contribute various functions in plants including, act as antioxidants and as natural defensive against plant pathogenic microorganismsThe purpose of this study was to evaluate the present secondary metabolites in healthy and diseased plant (infected by Fusarium decemcellulare) employing UPLC-QTOF-MSE combined with multivariate statistical analysis, chemometrics. The characteristic fingerprint was carried out in the negative ESI mode being observed deprotonation of molecules ([M-H]). A total of 10 secondary metabolites have been identified in samples of guarana sheet. The principal component analysis (PCA) showed significant differences between healthy and diseased sample. The metabolites responsible for the differentiation were analyzed by Orthogonal Partial Least Squares - Discriminant Analysis (OPLS-DA). The application of chemometric techniques has enabled the identification of biomarkers main biotic stress, being epicatechin the biomarker found in healthy plant and diseased plants the identified biomarkers were dimer procyanidin B-type and A, probably responsible for the response to biotic stress.After the discrimination of metabolites was identified catechin, epicatechin, dimer type B and A procyanidin and trimer type A procyanidin as the main metabolite responsible for the breakdown of the plant samples.